2006
DOI: 10.1093/annonc/mdl060
|View full text |Cite
|
Sign up to set email alerts
|

Current treatment options and biology of peritoneal mesothelioma: meeting summary of the first NIH peritoneal mesothelioma conference

Abstract: Peritoneal mesothelioma is a rare cancer of the peritoneum with about 250 new cases diagnosed each year in the United States. It is the second most common site for mesothelioma development and accounts for 10-20% of all mesotheliomas diagnosed in the United States. A meeting sponsored by the NIH Office of Rare Diseases was held in Bethesda, Maryland on September 13 and 14, 2004. The objective of this meeting was to review the epidemiology, biology and current surgical and medical management of peritoneal mesot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 20 publications
0
53
0
2
Order By: Relevance
“…This literature includes a systematic review and a meta-analysis [30,31]. A multidisciplinary conference in 2006 at the National Institutes of Health sponsored by the National Organization for Rare Diseases concluded that CRS plus perioperative chemotherapy may be considered by the multidisciplinary team as an initial treatment plan for patients with MPM [32]. The Peritoneal Surface Oncology Group International (PSOGI) consensus conference in 2008 declared CRS and perioperative chemotherapy as the standard of care for this disease realizing that knowledgeable selection of patients for such an aggressive treatment plan is necessary [33].…”
Section: Normothermic Intraperitoneal Chemotherapy Long Term For Malimentioning
confidence: 99%
“…This literature includes a systematic review and a meta-analysis [30,31]. A multidisciplinary conference in 2006 at the National Institutes of Health sponsored by the National Organization for Rare Diseases concluded that CRS plus perioperative chemotherapy may be considered by the multidisciplinary team as an initial treatment plan for patients with MPM [32]. The Peritoneal Surface Oncology Group International (PSOGI) consensus conference in 2008 declared CRS and perioperative chemotherapy as the standard of care for this disease realizing that knowledgeable selection of patients for such an aggressive treatment plan is necessary [33].…”
Section: Normothermic Intraperitoneal Chemotherapy Long Term For Malimentioning
confidence: 99%
“…Not all cancers behave equally, and how drugs kill cancer cells varies greatly. We may need to make adjustments for some cancers such as gastrointestinal stromal tumor (GIST) or mesothelioma (8)(9)(10)(11). In GIST, for example, investigators incorporated tumor density on computed tomographic (CT) scan and one-dimensional measurement of tumor lesions in their assessment of a population of patients who were divided into good and poor responders by the criterion of a decrease in standardized uptake value (SUV) of <2.5 measured by 2[18F]fluoro-2-deoxy-D-glucose (FDG)-positron emission tomography (PET).…”
Section: Desist Using Recist? the Issuesmentioning
confidence: 99%
“…Other findings include ascites, infiltrating mass involving the serous of the bowels, direct invasion within the liver, spleen and abdominal wall, retroperitoneal adenopathies and metastasis at distance. 30 The pelvic involvement can suitably be evaluated by ultrasound as well as a small amount of liquid at cul-de-sac. 19 Few data has been published about the magnetic resonance imaging and PET-CT imaging manifestations.…”
Section: Diagnosismentioning
confidence: 99%